Drug Oxidation by Cytochrome P450BM3: Metabolite Synthesis and Discovering New P450 Reaction Types. Issue 42 (27th August 2015) - Ren, Xinkun; Yorke, Jake A.; Taylor, Emily; Zhang, Ting; Zhou, Weihong; Wong, Luet Lok
Abstract There is intense interest in late‐stage catalytic CH bond functionalization as an integral part of synthesis. Effective catalysts must have a broad substrate range and tolerate diverse functional groups. Drug molecules provide a good test of these attributes of a catalyst. A library of P450BM3 mutants developed from four base mutants with high activity for hydrocarbon oxidation produced human metabolites of a panel of drugs that included neutral (chlorzoxazone, testosterone), cationic (amitriptyline, lidocaine) and anionic (diclofenac, naproxen) compounds. No single mutant was active for all the tested drugs but multiple variants in the library showed high activity with each compound. The high conversions enabled full product characterization that led to the discovery of the new P450 reaction type of oxidative decarboxylation of an α‐hydroxy carboxylic acid and the formation a protected imine from an amine, offering a novel route to α‐functionalization of amines. The substrate range and varied product profiles suggest that this library of enzymes is a good basis for developing late‐stage CH activation catalysts.